2011
DOI: 10.4244/eijv6i7a139
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a phase IIa, randomised, open-label trial to evaluate the percutaneous intramyocardial transplantation of autologous skeletal myoblasts in congestive heart failure patients: the SEISMIC trial

Abstract: Aims: The SEISMIC study was an open-label, prospective, randomised study to assess the safety and feasibility of percutaneous myoblast implantation in heart failure patients with implanted cardioverter-defibrillators (ICD). Methods and results: Patients were randomised 2:1 to autologous skeletal myoblast therapy vs. optimal medical treatment. The primary safety end-point was defined as the incidence of procedural and device related serious adverse events, whereas the efficacy endpoints were defined as the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 16 publications
4
61
0
Order By: Relevance
“…20 One trial administered cardiac stem cells, obtained from a right atrial appendage biopsy followed by magnetic separation and culture of c-kit-positive cells. 49 The remaining 4 trials isolated SM from muscle biopsies followed by culture of the cells ex vivo and identification of a SM population 37,42,44,51 containing ≥50% of CD56-positive cells. 37,42,51 Finally, 1 trial administered adipose-derived regenerative cells obtained by liposuction and followed by enzymatic digestion of the adipose tissue, cell separation, and cell elution using commercially available devices.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 One trial administered cardiac stem cells, obtained from a right atrial appendage biopsy followed by magnetic separation and culture of c-kit-positive cells. 49 The remaining 4 trials isolated SM from muscle biopsies followed by culture of the cells ex vivo and identification of a SM population 37,42,44,51 containing ≥50% of CD56-positive cells. 37,42,51 Finally, 1 trial administered adipose-derived regenerative cells obtained by liposuction and followed by enzymatic digestion of the adipose tissue, cell separation, and cell elution using commercially available devices.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
“…49 The remaining 4 trials isolated SM from muscle biopsies followed by culture of the cells ex vivo and identification of a SM population 37,42,44,51 containing ≥50% of CD56-positive cells. 37,42,51 Finally, 1 trial administered adipose-derived regenerative cells obtained by liposuction and followed by enzymatic digestion of the adipose tissue, cell separation, and cell elution using commercially available devices. 21 The cell dose ranged from 5×10 Fifteen trials compared cells with a placebo, 9,11,21,22,28,29,[31][32][33][34][35]42,44 generally consisting of a cell-free solution, either the participants own serum or a saline solution containing heparin.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Among these treatments, using autologous skeletal myoblasts has been investigated in clinical trials, mainly in Western countries, in which cell transplantation was performed using myocardial injection during a surgical procedure through a thoracotomy, such as coronary artery bypass grafting (CABG) or LVAS implantation, 4 or using myocardial injection of cells through a cardiac catheter. 5 However, results from a European phase II clinical study (MAGIC trial) demonstrated that transplantation ver the past 20 years or so, the treatment of chronic heart failure (HF) has been progressed by use of drug therapies such as β-blockers, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin II receptor blockers (ARBs), and aldosterone antagonists, or device therapy such as cardiac resynchronization therapy. Hence, clinical outcomes of patients with chronic HF are now significantly better, but patients with severe chronic HF who do not respond well to standard drug therapies still have poor outcomes.…”
mentioning
confidence: 99%
“…human and animal models, to varying degrees of success [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In animal models, these cellbased therapies have demonstrated effectiveness in reducing infarct size and ventricular dilatation, and improving myocardial function [24][25][26] .…”
Section: Figurementioning
confidence: 99%